Cardiovascular profile of patients with chronic kidney disease - Mahishale, G. S.; Allolli, Deepa; Patil, Anand; G., Basavaraj P.; Shetagar, Sachin; Talikoti, Satish (International Journal of Research in Medical Sciences, 2019)
Background: Frequency of fatal and nonfatal cardiovascular events increase even in early stages of chronic kidney disease (CKD). This study was aimed to understand the cardiovascular profile of patients with CKD. Methods: This observational study was conducted on patients who were admitted with chronic kidney disease in Sri Venkateswara Rama Narayan RUIA Government General Hospital, Tirupati. Patients were classified according to their severity of CKD. All patients had an electrocardiogram and echocardiogram. Results of various biochemical investigations, electrocardiogram and echocardiogram were compared between patients with mild, moderate and severe CKD. Results: Combined diabetes mellitus and hypertension was found to be the most common case of CKD in Authors patient population (43%), followed by diabetes mellitus alone (37%). Serum creatinine and blood urea nitrogen were found to be significantly higher and creatinine clearance and haemoglobin were significantly lower among patients with severe CKD. Electrocardiography revealed 50% had left ventricular hypertrophy (LVH), 30% had tall ‘T’ waves and 15 % had ST-segment changes. Mean inter-ventricular septal end diastole thickness and mean left ventricular mass was found to be significantly in patients with severe CKD as compared to mild CKD. Conclusions: Extensive cardiovascular evaluation of patients with CKD is warranted even if the classical symptoms are not absent and early cardiovascular rehabilitation should be instituted in such patients.